2019
DOI: 10.1007/s10924-019-01436-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Citric Acid on Physicochemical Properties of Hydrophilic Carboxymethyl Starch-Based Films

Abstract: The carboxymethyl starch-based films in a presence of citric acid were prepared by casting technique. The influence of citric acid content on physicochemical properties of obtained hydrophilic films were evaluated (solubility in water, moisture absorption, mechanical and thermal properties). The crosslinking of starch derivative chains has been confirmed by FTIR spectroscopy, however, an excess of citric acid could cause hydrolysis of carboxymethyl starch chains. The best mechanical performance has been noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Chitosan is insoluble in deionized water at neutral pH, however starch, because of its hydrophilicity, may be partially soluble. The low gel content of starch hydrogel indicates that probably some amount of unreacted CA and its excess were present leading to CA‐modified starch acidolysis . It has been reported that the reduction of starch chains could occur at low pH .…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan is insoluble in deionized water at neutral pH, however starch, because of its hydrophilicity, may be partially soluble. The low gel content of starch hydrogel indicates that probably some amount of unreacted CA and its excess were present leading to CA‐modified starch acidolysis . It has been reported that the reduction of starch chains could occur at low pH .…”
Section: Resultsmentioning
confidence: 99%
“…318,324 It is also used for the development of different materials as biodegradable polymers whose properties including the mechanical ones have been investigated. [325][326][327][328][329][330][331][332][333][334][335][336][337][338][339][340][341] 2.4.1 Crystal structure. The optimized crystal structure of anhydrous citric acid, COOH-CH 2 -C(OH)(COOH)-CH 2 -COOH, is drawn in Fig.…”
Section: Anhydrous Citric Acidmentioning
confidence: 99%
“…In‐situ crosslinking can increase mechanical strength by forming ester bonds between CA and citric acid. However, higher concentration of citric acid (15%) causes excess crosslinking and limited mobility of polymer chain which results in reduced tensile modulus of the fibers 53 …”
Section: Resultsmentioning
confidence: 99%